A multicentre cross-sectional observational study of cancer multidisciplinary teams: Analysis of team decision making - Soukup,T; Lamb,BW; Morbi,A; Shah,NJ; Bali,A; Asher,V; Gandamihardja,T; Giordano,P; Darzi,A; Green,JSA; Sevdalis,N (Cancer Medicine, 2020)
BackgroundMultidisciplinary teams (MDT) formulate expert informed treatment recommendations for people with cancer. We set out to examine how the factors proposed by the functional perspective of group decision making (DM), that is, interaction process, internal factors (factors emanating from within the group such as group size), external circumstances (factors coming from the outside of the team), and casecomplexity affect the quality of MDT decision making.MethodsThis was a crosssectional observational study. Three cancer MDTs were recruited with 44 members overall and 30 of their weekly meetings filmed. Validated observational instruments were used to measure quality of DM, interactions, and complexity of 822 case discussions.ResultsThe full regression model with the variables proposed by the functional perspective was significant, R2 = 0.52, F(20, 801) = 43.47, P < .001, adjusted R2 = 0.51. Positive predictors of DM quality were asking questions (P = .001), providing answers (P = .001), team size (P = .007), gender balance (P = .003), and clinical complexity (P = .001), while negative socioemotional reactions (P = .007), gender imbalance (P = .003), logistical issues (P = .001), timeworkload pressures (P = .002), and time spent in the meeting (P = .001) were negative predictors. Second half of the meetings also saw significant decrease in the DM quality (P = .001), interactions (P = .001), group size (P = .003), and clinical complexity (P = .001), and an increase in negative socioemotional reactions (P = .001) and timeworkload pressures (P = .001).DiscussionTo the best of our knowledge, this is the first study to attempt to assess the factors proposed by the functional perspective in cancer MDTs. One novel finding is the effect of sociocognitive factors on team DM quality, while another is the cognitivecatch 22 effect: while the case discussions are significantly simpler in the second half of the meeting, there is significantly less time left to discuss